Characterization of Genetic Differences within the Centrally Projecting Edinger–Westphal Nucleus of C57BL/6J and DBA/2J Mice by Expression Profiling - Giardino, William J.; Cote, Dawn M.; Li, Ju; Ryabinin, Andrey E. (Frontiers in Neuroanatomy, 2012)
Detailed examinations of the midbrain Edinger-Westphal nucleus (EW) revealed the existence of two distinct nuclei. One population of preganglionic neurons was found to control oculomotor functions (EWpg), and a separate population of centrally-projecting neurons was found to contain stress- and feeding-related neuropeptides thought to be important for drug and alcohol addiction (EWcp). Although we and others have shown that neurons of the EWcp are highly responsive to drugs of abuse and behavioral stress, a thorough genetic characterization of the EWcp was needed. In order to identify genetic differences in the EWcp between mouse strains that differ in behaviors relevant to EWcp function, we used publicly-available tools from the Allen Brain Atlas to identify 68 genes that were selectively-expressed in the EWcp, and examined their expression within tissue punch microdissection samples containing the EWcp of adult male C57BL/6J (B6) and DBA/2J (D2) mice. Using 96-well quantitative real-time PCR (qPCR) arrays that included the EWcp-specific genes, several other genes of interest, and five housekeeping genes, we found strain differences in expression of eleven EWcp-specific genes (BC023892, Btg3, Bves, Cart, Cck, Ghsr, Neto1, Postn, Ptprn, Rcn1, and Ucn), two immediate early genes (Egr1 and Fos), and one dopamine-related gene (Drd5). All significant expression differences were greater in B6 vs. D2 mice, and several of these were verified at the protein level using immunohistochemical (IHC) protocols. These results demonstrate a significant advance in our understanding of the EWcp on three levels. First, we generated a list of EWcp-specific genes (most of which had not yet been reported within the EWcp in the literature) that will be informative for future studies of EWcp function. Second, due to similarity in results from qPCR and IHC, we revealed that strain differences in basal EWcp neuropeptide content are accounted for by differential transcription and by the numbe